If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -7) = 6(5 + 9) + 4 Reorder the terms: 2(-7 + 3x) = 6(5 + 9) + 4 (-7 * 2 + 3x * 2) = 6(5 + 9) + 4 (-14 + 6x) = 6(5 + 9) + 4 Combine like terms: 5 + 9 = 14 -14 + 6x = 6(14) + 4 Multiply 6 * 14 -14 + 6x = 84 + 4 Combine like terms: 84 + 4 = 88 -14 + 6x = 88 Solving -14 + 6x = 88 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 6x = 88 + 14 Combine like terms: -14 + 14 = 0 0 + 6x = 88 + 14 6x = 88 + 14 Combine like terms: 88 + 14 = 102 6x = 102 Divide each side by '6'. x = 17 Simplifying x = 17
| -7=1/5x | | 4ax+b=12bx+40b | | 4/5x^2y,8/3xy,12/13xy^5 | | 2(5x-1)=8(x+1) | | 2x^2+3x+j=0 | | 7t^2-112= | | 3y-1=2y-5 | | n=3.64+12 | | 60x^3+24x^2-360x-144= | | 3y+5-7y-7= | | 30x-15x=150 | | -11+x=4 | | 25k^2+81= | | -5/0 | | 4x+12=x+14-12 | | 9r^2+30r+25= | | x^2-64=12x | | 2sin(2x-1)=0 | | 4x+12=x+14 | | 3/5-4/5 | | 21=-3/8× | | x=.6+384 | | 2x+3=5x+97 | | 7=-7/5x-7 | | y=-7/5(-5)-7 | | 64c^2-25t^2= | | 73/5-4/5 | | y=-7/5(0)-7 | | y=-7/5x-7 | | 4=x*7+86/2 | | 25w^2-120w+144= | | 4y+1=3y-2 |